2016
DOI: 10.1039/c6rp00005c
|View full text |Cite
|
Sign up to set email alerts
|

Write on the edge: using a chemistry corpus to develop academic writing skills resources for undergraduate chemists

Abstract: Many undergraduate students find the production of an extended piece of academic writing challenging. This challenge is more acute in the sciences where production of extended texts is infrequent throughout undergraduate studies. This paper reports the development of a new English for Academic Purposes (EAP) workshop and associated resources for third year undergraduate chemists to support their dissertation module. The workshop is designed to utilise a searchable database of student texts (a corpus) developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…The RELT had the least retention and it is concluded that active engagement using the box-bead-analogy leads to better retention of chemical kinetics concepts. The findings of this study are in agreement with several related research studies (Taylor et al, 2016;Shahani & Jenkinson, 2016;D'Ottone & Ochonogor, 2017) that concluded that when students engage with analogies they form concrete analogues that enhances retention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The RELT had the least retention and it is concluded that active engagement using the box-bead-analogy leads to better retention of chemical kinetics concepts. The findings of this study are in agreement with several related research studies (Taylor et al, 2016;Shahani & Jenkinson, 2016;D'Ottone & Ochonogor, 2017) that concluded that when students engage with analogies they form concrete analogues that enhances retention.…”
Section: Discussionsupporting
confidence: 92%
“…The findings focused on conceptual knowledge and left out the procedural knowledge. Shahani and Jenkinson (2016) also explored the efficacy of interactive analogical models among third-year chemistry students. The study employed two analogies: the spring system and electrostatic spheres on potential energy curves.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that have used concordancing tools and on-line reference resources include (Zhang et al, 2017) that focused on the use of personally developed corpora to assist in academic writing development of postgraduate medical students. Bruce et al (2016) described student feedback to activities using concordancing as a resource for developing academic writing skills among Chemistry undergraduate students and Romer and Wulff (2010) examined the use of specific linguistic structures (demonstrative pronouns) in different disciplinary corpus subsets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers suggest that in Google-assisted language learning, Internet search engines serve as concordancing tools (Acar, 2011;Bruce, Coffer, Rees, & Robson, 2016;Conroy, 2010;Geluso, 2013;Panah, Yunus, & Embi, 2013;Shei, 2008;Zhang, Zheng, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation